Growth and Nutrient Uptake of Maize Plants as affected by Elemental Sulfur and Nitrogen Fertilizer in Sandy Calcareous Soil - Motior Rahman, M.; Soaud, A.A.; Darwish, F.H.A.; Golam, F.; Sofian-Azirun, Mohd (Academic Journals, 2011)
This study was carried out to investigate the effect of elemental sulfur (S 0) combined with or without N fertilizer on the growth and nutrient uptake such as nitrogen (N), phosphorus (P), sulfur (S), iron (Fe), zinc (Zn) and manganese (Mn) by maize plants grown in sandy calcareous soils. Elemental S at rates of 0, 1, 5 and 10 t ha -1 were tested combined with or without N fertilizer at rates of 0 and 0.34 t ha -1 in pots using normal irrigation water (pH >7.5) under Al Zaid and Al Semaih soils in evaporative cooled greenhouse conditions. Electrical conductivity (EC) increased (2.50 to 2.95 dSm -1) significantly and decreased (5.07 to 6.06 dSm -1) with application of S 0 at rates of 5 and 10 t ha -1 combined with N fertilizer in both Al Zaid and Al Semaih soils, respectively. Soil acidity improved by decreasing soil pH (1.41 to1.52 unit) with application of S 0 at the rate of 10 t ha -1 combined with N fertilizer. Addition of S 0 at the rate of 5 t ha -1 combined with N fertilizer recorded superior total dry matter (TDM) and maximum uptake of all nutrients in both soils. Total dry matter accumulation and nutrient uptake had positive correlation, while soil pH showed negative correlation with TDM and uptake of all nutrients. Based on experimental findings, S 0 at the rate of 5 t ha -1 combined with N fertilizer is suitable for growth of maize in both soils. Collectively, the results indicate that Al Zaid soil is more favorable due to higher nutrient uptake and growth of maize than Al Semaih soil. Â© 2011 Academic Journals.